INTEGRATED CHARACTERISTIC BASE OF MODULAR NUMBER SYSTEMS - A. A. Kolyada; A. F. Chernyavsky (Informatika)
The problem of development of an integrated characteristic base of a modular number system defined on the ranges of non-negative integers is studied. A mechanism of interval-modular forms of integer numbers is applied to solve this problem. Interval index characteristics – the interval index and the main interval index - play a key role in this mechanism. Priority of these characteristics is explained by their essential advantages over known integrated characteristics of a modular code when optimizing algorithms of non-modular operations.